ADAS Authentic Data Allowed Security In Internet Of Things - et. al., Raveena Yadav, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With the growing of population, things and networks, things connectivity is also taking a graph in exponential manner. This whole connectivity makes a whole network that is known as Internet of Things. But these devices are prone to cyber-attacks, so, security is one of the apex concerns and challenge for internet of things. Main motivation of writing this paper is that security is the main concern whether it is internet or internet of things. In this paper, we have proposed a model Authentic Data Allowed Security, in which only authentic packets are allowed to enter and usable by node and all other packets will be dropped by the router